2002
DOI: 10.1039/b205279m
|View full text |Cite
|
Sign up to set email alerts
|

Cement-polymer and clay-polymer nano- and meso-composites: spotting the difference

Abstract: Calcium silicate hydrate (C-S-H), the most important reaction product of Portland cement with water, is a layered lattice silicate which has much in common with smectite clays. Both materials may be synthesised (C-S-H) or found in nature (smectites) in the form of particles which are stacks of negatively charged nanometre-thick platelets separated by water molecules and charge-compensating cations. Smectite clays are well known for their ability to intercalate molecular species including polymers, to ''swell''… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 38 publications
4
47
2
1
Order By: Relevance
“…Such analysis can be used, for example, to assess the gel-pore ratio and initial water-to-cement ratio of an existing sample of cement. The structure of gel pores can change due to drying, load, or even deliberate alteration such as by filling these (10-100)-nm-scale spaces with polymer [76]. Since such a change in structure will greatly influence properties, our proposed technique for assessing the gel pore structure can be a valuable research tool.…”
Section: Discussionmentioning
confidence: 99%
“…Such analysis can be used, for example, to assess the gel-pore ratio and initial water-to-cement ratio of an existing sample of cement. The structure of gel pores can change due to drying, load, or even deliberate alteration such as by filling these (10-100)-nm-scale spaces with polymer [76]. Since such a change in structure will greatly influence properties, our proposed technique for assessing the gel pore structure can be a valuable research tool.…”
Section: Discussionmentioning
confidence: 99%
“…The plateau of the isotherm is on the order of 1 ± 0.5 µmol g −1 , which is really at the detection limit in our experimental conditions and which, considering the surface area of C-S-H, is very small. Indeed, the surface area of C-S-H readily accessible to water molecules, as measured by NMR relaxation for instance, is on order of 100 m 2 /g [28,29] (this does not take into account the interlayer surface area, which is not accessible to neutral p(EO) chains [30]). Thus, the maximum surface concentration of TX100 adsorbed is on the order of 0.01 µmol/m 2 .…”
Section: Surfactant Adsorptionmentioning
confidence: 99%
“…doi:10.1016/j.msea.2010.07.057 one of the most viable for producing C-S-H/polymer nanocomposites [6]. However, Merlin et al [11] observed no evidence of PDC intercalation and suggest that this polymer is adsorbed on the surface or in the void space left by the crystallites stacks, forming a mesocomposite.…”
Section: Introductionmentioning
confidence: 96%